Organic silicon heat insulation coating and preparation method thereof
By combining components A and B in the silicone thermal insulation coating formulation with nano-expanded graphite and PCL phase change material, a porous structure and insulating layer are formed, which solves the problem of insufficient thermal insulation and insulation of existing coatings at high temperatures, and achieves safe thermal insulation and insulation effect for batteries at high temperatures.
Patent Information
- Application Number
- CN202411660704.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing coatings are either heat-resistant but not heat-insulating, or heat-insulating but not heat-resistant, which cannot meet the high-temperature resistance requirements of the battery field in the temperature range of 600 to 1500°C. Furthermore, heat-insulating coatings may lose their insulation properties at high temperatures, leading to safety accidents such as battery leakage and short circuits.
The formulation of the silicone thermal insulation coating includes component A and component B. Through the combination of vinyl silicone oil and phenyl vinyl silicone rubber, functional powders such as nano-expanded graphite, hollow glass microspheres and PCL phase change material are added to form a loose porous structure and dense surface at the micron scale, which improves thermal insulation and flame retardancy. An insulating layer is added to the components to maintain insulation.
It achieves excellent heat insulation, flame retardancy and insulation properties at high temperatures, making it suitable for the battery industry. It can maintain battery safety within a temperature range of 600 to 1500°C, preventing battery leakage and short circuits.
Smart Images

Figure CN119432230A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coatings applied to batteries, and in particular to an organic silicon thermal insulation coating and a preparation method thereof. Background Art
[0002] Paint refers to a material that is applied to the surface of an object to be protected or decorated and can form a continuous film that is firmly attached to the object. In other words, paint is a material that can be applied to the surface of an object using different construction processes to form a solid film that is firmly adhered, has a certain strength, and is continuous.
[0003] In particular, in the field of batteries, coatings play a very important role and are widely used, such as carriers for electrochemically active materials, coatings for isolation materials, protection of battery housings, and thermal management. By improving the conductivity, insulation, and corrosion resistance of batteries, the overall performance and reliability of batteries are significantly improved. In recent years, with the rise of emerging industries such as renewable energy and electric vehicles, the requirements for battery performance and safety have become increasingly higher, which has promoted further innovation in battery coating technology. New types of coatings such as smart coatings and high-temperature resistant coatings continue to emerge, providing guarantees for the use of batteries in extreme environments.
[0004] However, the coatings in the prior art are either high-temperature resistant but not heat-insulating, or heat-insulating but not high-temperature resistant. High-temperature resistant but not heat-insulating coatings are made by adding high-temperature resistant fillers to the formula to achieve the effect of high temperature resistance, but such materials do not have heat-insulating properties. The lack of heat-insulating properties in the coating will cause the battery temperature to be too high, which may increase the risk of battery overheating, etc. Heat-insulating but not high-temperature resistant coatings, such coatings may be damaged due to excessive temperature in a high-temperature environment, such as melting, softening or decomposition, thereby losing their protective effect on the battery. For example, polyurethane coatings work on the principle of heat insulation by thermal decomposition at high temperatures. However, due to the thermal decomposition of the coating, it loses its own insulation and has electrical conductivity. For coatings applied to battery casings, if they have electrical conductivity, a series of safety accidents such as battery leakage and short circuit will occur. Therefore, it is desired to provide a coating that has both high-temperature resistance and heat-insulating properties, and the coating has good insulation properties and can be used to be applied to battery casings.
[0005] At present, thermal insulation coatings are mainly divided into two categories: expansion type and non-expansion type. Expansion type includes polyurethane, epoxy, polyurea, acrylic, etc. The characteristics of expansion type thermal insulation coatings are: under high temperature, the carbon source and gas source in the coating work together to foam at a foaming ratio of 10-30 times, forming a thick foamed carbon layer, thereby blocking oxygen and heat transfer, and playing a role in fireproofing and heat insulation. The advantages of this type of coating are good thermal insulation performance and low cost. The disadvantage is that there must be a foaming expansion space to form a foamed carbon layer to play a role, and the strength of the foamed carbon layer is not high, and it is not resistant to flames and airflow erosion. Non-expansion type thermal insulation coatings include silicates, silicones, silica sols, organic-inorganic hybrids and aerogel water-based fireproof and heat-insulating coatings. Among them, silicate and silica sol thermal insulation coatings are brittle, hard and have poor thermal insulation performance, and cannot meet the needs of power batteries with pressure and rebound; aerogel water-based coatings have good thermal insulation performance, but poor mechanical properties. In the prior art, the mechanical properties of the coating are improved by increasing the proportion of organic phase, but it has a great impact on the thermal insulation performance; and silicone thermal insulation coatings have good temperature resistance and good resilience because of silicone itself. However, the current silicone thermal insulation coatings generally have a high temperature resistance range of about 200°C, and thermal decomposition occurs at 500-600°C, which cannot meet the high temperature resistance range of 600-1500°C in the battery field. Therefore, it is necessary to conduct in-depth research on silicone thermal insulation coatings so that silicone thermal insulation coatings have a high temperature resistance range that meets the needs of the battery field, while having good thermal insulation performance and good insulation. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an organosilicon thermal insulation coating and a preparation method thereof.
[0007] In a first aspect, an embodiment of the present invention discloses an organosilicon thermal insulation coating, including a component A and a component B;
[0008] In parts by mass, the component A includes: 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 parts of inhibitor, and 1 to 10 parts of PCL phase change material;
[0009] In parts by mass, the B component includes: 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 parts of catalyst, and 1 to 10 parts of PCL phase change material;
[0010] The surfaces of the nano-expanded graphite in the A component and the B component have an insulating layer; and the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
[0011] By adopting the above technical scheme, firstly, the heat insulation ability of the coating is improved by the combination of vinyl silicone oil and phenyl vinyl silicone rubber, and the coating has good mechanical properties. By using other functional powders, the heat insulation coating has a higher residual carbon content and a dense surface state at high temperature, and has a good heat insulation effect. Because the glass powder and hollow glass microspheres melt at high temperature and cause volume collapse, the nano-expanded graphite can produce a volume expansion of 2-5 times under high temperature, forming a loose porous structure of micrometer scale, which can effectively fill the aforementioned collapsed volume and increase the cavity ratio of the ceramic coating. At the same time, the carbon layer formed can also further reduce the thermal conductivity, improve the heat insulation and flame retardant ability. A heat insulation coating with both high temperature resistance and heat insulation performance suitable for the battery field is obtained, and has good flame retardant ability, and the surface of the expanded graphite has an insulating layer to ensure the insulation of the silicone heat insulation coating of the present invention. And the silicone heat insulation coating of the present invention includes component A and component B, which is convenient for regulating the viscosity of component A and component B during the preparation process, which is beneficial to improve the curing film-forming performance of the silicone heat insulation coating of the present invention and is convenient for storage, and has better processability.
[0012] Optionally, in parts by mass, the component A further comprises: 5 to 15 parts of nano titanium dioxide, 5 to 15 parts of nano aluminum hydroxide, and the component B further comprises: 5 to 15 parts of nano titanium dioxide, 5 to 15 parts of nano aluminum hydroxide.
[0013] Optionally, the component A further comprises, by weight, 0.1 to 1.5 parts of a silane coupling agent and 0.05 to 1 parts of red iron oxide; and the component B further comprises 0.1 to 1.5 parts of a silane coupling agent.
[0014] Optionally, the component A and the component B satisfy at least one of the following conditions:
[0015] The particle size of the wollastonite is 5 to 20 μm, and the aspect ratio of the wollastonite is 10:1 to 30:1;
[0016] The mica powder comprises mica powder 1 and mica powder 2, the mass ratio of the mica powder 1 to the mica powder 2 is 1:1 to 3:1, the particle size of the mica powder 1 is 15 to 30 μm, and the particle size of the mica powder 2 is 1 to 10 μm;
[0017] The glass powder includes glass powder 1 and glass powder 2, the mass ratio of the glass powder 1 to the glass powder 2 is 3:1-6:1, the particle size of the glass powder 1 is 1-5 μm, and the particle size of the glass powder 2 is 15-30 μm;
[0018] The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
[0019] Optionally, in the component A, the particle size of the nano-expanded graphite is 600-900 nm; in the component B, the particle size of the nano-expanded graphite is 600-900 nm; the particle sizes of the nano-expanded graphite in the component A and the component B are equal.
[0020] Optionally, in the component A and the component B, the melting point of the glass powder 1 is 380-450°C, and the melting point of the glass powder 2 is 500-600°C.
[0021] Optionally, in the component A and the component B,
[0022] The vinyl silicone oil comprises vinyl silicone oil 1 and vinyl silicone oil 2, wherein the viscosity of the vinyl silicone oil 1 is 2000-5000 mPa·s, and the viscosity of the vinyl silicone oil 2 is 8000-200000 mPa·s; the mass content of vinyl in the vinyl silicone oil is 0.03%-2.3%; in terms of mass parts, in component A, the vinyl silicone oil comprises 10-20 parts of the vinyl silicone oil 1 and 10-20 parts of the vinyl silicone oil 2, and in component B, the vinyl silicone oil comprises 10-30 parts of the vinyl silicone oil 1 and 10-20 parts of the vinyl silicone oil 2;
[0023] The viscosity of the phenyl vinyl silicone rubber is 6000-200000 mPa·s, the mass content of vinyl in the phenyl vinyl silicone rubber is 0.1%-0.75%, the molar content of phenyl is 3%-25%, and the mass content of the phenyl vinyl silicone rubber in the component A and / or the component B is 10%-15%;
[0024] The hydrogen content of the hydrogen-containing silicone oil is 0.5wt% to 2.5wt%.
[0025] In a second aspect, an embodiment of the present invention discloses a method for preparing an organosilicon thermal insulation coating, which is used to prepare an organosilicon thermal insulation coating as in any embodiment of the first aspect, comprising the following steps:
[0026] Preparation of component A: by weight, 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 parts of inhibitor and 1 to 10 parts of PCL phase change material are mixed to obtain component A;
[0027] Preparation of component B: by weight, 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 part of catalyst and 1 to 10 parts of PCL phase change material are mixed to obtain component B;
[0028] Preparation of organic silicon thermal insulation coating: mixing and curing the component A and the component B to obtain the target organic silicon thermal insulation coating;
[0029] Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
[0030] The above technical solution has better processability, and the preparation process is simple and efficient, which makes it easy to prepare silicone thermal insulation coatings that have both high temperature resistance and heat insulation properties and have good flame retardancy and insulation properties.
[0031] Optionally, at least one of the following conditions is met in the steps of preparing component A and preparing component B:
[0032] The particle size of the wollastonite is 5 to 20 μm, and the aspect ratio of the wollastonite is 10:1 to 30:1;
[0033] The mica powder comprises mica powder 1 and mica powder 2, the mass ratio of the mica powder 1 to the mica powder 2 is 1:1 to 3:1, the particle size of the mica powder 1 is 15 to 30 μm, and the particle size of the mica powder 2 is 1 to 10 μm;
[0034] The glass powder includes glass powder 1 and glass powder 2, the mass ratio of the glass powder to the glass powder 2 is 3:1-6:1, the particle size of the glass powder 1 is 1-5 μm, the particle size of the glass powder 2 is 15-30 μm, the melting point of the glass powder 1 is 380-450° C., and the melting point of the glass powder 2 is 500-600° C.;
[0035] The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
[0036] Optionally, the method for preparing the organosilicon thermal insulation coating comprises the following steps:
[0037] Powder modification: mixing a silane coupling agent, water, ethanol and 5wt% ammonia water to obtain a mixed solution of the silane coupling agent, water, ethanol and 5wt% ammonia water, mixing 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide by weight, adding the mixture of the silane coupling agent, water, ethanol and 5wt% ammonia water to mix by using a jet mill to obtain modified 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide powder;
[0038] Preparation of component A: After mixing 10 to 20 parts of vinyl silicone oil 1, 10 to 20 parts of vinyl silicone oil 2 and 10 to 20 parts of phenyl vinyl silicone rubber, add 5 to 15 parts of modified wollastonite, 2 to 8 parts of mica powder 1, 1 to 4 parts of mica powder 2, 5 to 10 parts of glass powder 1, 1 to 4 parts of glass powder 2, 0.5 to 2 parts of nano expanded graphite, 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide powder, and heat to dehydrate. After cooling to stop dehydration, add 1 to 10 parts of hydrogen-containing silicone oil and 0.1 to 1 part of inhibitor at a constant temperature, and then add 5 to 10 parts of hollow glass microspheres 1, 1 to 5 parts of hollow glass microspheres 2, 0.05 to 1 part of red iron oxide and 1 to 10 parts of PCL phase change material to obtain component A;
[0039] Preparation of component B: by weight, 10 to 30 parts of vinyl silicone oil 1, 10 to 20 parts of vinyl silicone oil 2 and 10 to 15 parts of phenyl vinyl silicone rubber are mixed, and then 5 to 15 parts of the modified wollastonite, 2 to 8 parts of mica powder 1, 1 to 4 parts of mica powder 2, 5 to 10 parts of glass powder 1, 1 to 4 parts of glass powder 2, 0.5 to 2 parts of nano expanded graphite, 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide powder are added, and then 5 to 10 parts of hollow glass microspheres 1 and 1 to 5 parts of hollow glass microspheres 2 are added, and the mixture is heated and dehydrated, and after the temperature is lowered to stop the dehydration, 1 to 10 parts of PCL phase change material are added at a constant temperature and mixed, and 0.1 to 1 part of catalyst is added and mixed to obtain component B;
[0040] Preparation of organic silicon thermal insulation coating: after mixing the component A and the component B, spraying them on the surface of the template and curing them, to obtain the target organic silicon thermal insulation coating;
[0041] Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The temperature rise curves of the back side of the 1 mm coating at 900° C. are shown for Example 1, Example 2 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0043] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0044] It should be noted that in this specification, similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings.
[0045] The terms “first”, “second”, etc. are only used for distinguishing descriptions and should not be understood as indicating or implying relative importance.
[0046] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0047] Although there are already many coatings in the prior art, the inventors have found through research that the coatings in the prior art are either resistant to high temperatures but not heat-insulating, or heat-insulating but not resistant to high temperatures. Even the existing thermal insulation coatings lose their original insulation in order to exert their thermal insulation properties, which will cause a series of safety accidents such as battery leakage and short circuit. In particular, silicone thermal insulation coatings have good temperature resistance and resilience because of silicone itself. However, the current silicone thermal insulation coatings generally have a high temperature resistance range of about 200°C, and thermal decomposition occurs at 500-600°C, which cannot meet the demand for a high temperature resistance range of 600-1500°C in the battery field. Therefore, the inventors hope to provide a silicone thermal insulation coating that has both high temperature resistance and thermal insulation properties, and the coating has good insulation properties and can be used in the battery field, such as coating on battery casings.
[0048] In a first aspect, an embodiment of the present invention discloses an organosilicon thermal insulation coating, including a component A and a component B;
[0049] Component A includes, by mass: 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 parts of inhibitor, and 1 to 10 parts of PCL phase change material;
[0050] Component B includes, by mass: 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 parts of catalyst, and 1 to 10 parts of PCL phase change material;
[0051] Among them, the surface of the nano-expanded graphite in component A and component B has an insulating layer; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters. Specifically, higher aliphatic hydrocarbons such as n-hexadecane, n-octadecane, microcrystalline wax, polyethylene wax; fatty acids such as stearic acid and palmitic acid. The PCL phase change material preferably has an outer coated spherical structure, and the phase change material can still maintain closed pores after endothermic melting. In addition, mica powder includes one or more of muscovite, phlogopite, sericite and fluorphlogopite; glass powder is, for example, boron glass.
[0052] The present invention improves the thermal insulation ability of the coating while having good mechanical properties by controlling the combination of vinyl silicone oil and phenyl vinyl silicone rubber in component A and component B in the formula of the organic silicon thermal insulation coating, and further controls the thermal insulation performance of the organic silicon thermal insulation coating of the present invention by using other powders. However, it is uncertain whether it can meet the high temperature resistance requirements in the battery field. The inventors have determined the above technical solution after various attempts and experiments.
[0053] The inventor discovered during the research that the combination of vinyl silicone oil and phenyl vinyl silicone rubber improves the heat resistance of the coating, but it still cannot meet the high temperature resistance requirements in the battery field. Furthermore, in components A and B, the curing rate is regulated by hydrogen-containing silicone oil, and the addition of powdered wollastonite, mica powder, and glass powder allows the silicone thermal insulation coating to be ceramicized, and then combined with the use of hollow glass microbeads as thermal insulation fillers, and PCL phase change materials that melt to form pores when the temperature is higher than the melting temperature of the PCL phase change material. Because the PCL phase change material has the function of absorbing energy on the one hand, and on the other hand, the pores formed by its melting can cooperate with the ceramicization system to form a new sealed space, it can further reduce heat conduction, so that the silicone thermal insulation coating has a higher residual carbon content and a dense surface state at high temperatures, and has good high temperature resistance and thermal insulation capabilities.
[0054] During the experiment, the inventor also found that the glass powder and hollow glass microspheres in the above-mentioned powder melted at high temperature and easily caused the volume collapse of the coating. The inventor added nano expanded graphite in component A and component B. Under the action of high temperature, the nano expanded graphite can produce 2-5 times of volume expansion and form a loose porous structure of micrometer scale. The porous structure formed by expansion can effectively fill the aforementioned collapsed volume and increase the cavity ratio of the ceramicized thermal insulation coating. At the same time, the carbon layer formed can also further reduce the thermal conductivity, improve the thermal insulation and flame retardant ability. However, the inventor considers that expanded graphite itself is easy to conduct electricity, so it must be processed before use, so that the surface of the nano expanded graphite in component A and component B has an insulating layer to avoid accidents such as battery leakage and short circuit caused by conduction. Specifically, the surface of the nano expanded graphite in component A and component B is coated with an insulating layer, and the insulating layer refers to a coating layer formed by the hydrolysis product of siloxane on its surface, such as the isolation layer formed by the hydrolysis product (silicon dioxide) of tetraethyl orthosilicate on the surface of expanded graphite.
[0055] The present invention obtains an organosilicon thermal insulation coating suitable for the battery field that has both high temperature resistance and heat insulation performance, and has good flame retardancy and insulation properties, by combining component A and component B in the above formula, with the range of each powder content set specifically as described above.
[0056] In addition, the formula of the silicone thermal insulation coating of the present invention includes component A and component B, which is convenient for regulating the viscosity of component A and component B respectively during the preparation process, and is beneficial to improving the curing and film-forming properties of the silicone thermal insulation coating of the present invention. Component A includes hydrogen-containing silicone oil and inhibitors as curing agents. The above-mentioned inhibitor refers to acetylene inhibitors, such as butynedioic acid esters or phenylacetylene, etc., which are used to inhibit the cross-linking and curing of the vinyl silicone oil and hydrogen-containing silicone oil in component A through silicon-hydrogen addition reaction. Component B includes a catalyst. Specifically, the catalyst is a platinum catalyst with a concentration of 5000ppm. The silicone thermal insulation coating of the present invention can only be prepared after component A and component B are mixed and cured, which is convenient for storage and has better processability.
[0057] Furthermore, by weight, component A also includes: 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide, and component B also includes: 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide. The inventors further improved the fireproof performance of the silicone thermal insulation coating by adding anti-radiation filler nano titanium dioxide and flame retardant nano aluminum hydroxide to components A and B, and matched them with the above-mentioned other powders, and improved the radiation resistance of the coating to improve the thermal insulation capacity, so as to protect adjacent batteries from the thermal runaway monomer cells from spreading thermal runaway.
[0058] Since the organic silicon thermal insulation coating of the present invention is obtained by the mutual coordination of the above-mentioned multiple powder fillers, and the powders are prone to agglomeration and other problems. In order to avoid the above problems, the component A of the present invention also includes: 0.1 to 1.5 parts of silane coupling agent by weight; the component B also includes: 0.1 to 1.5 parts of silane coupling agent. The silane coupling agent can reduce the thickening and agglomeration effect of the powder, and can enhance the dispersibility of the powder in vinyl silicone oil and phenyl vinyl silicone rubber, thereby improving the adhesion of the organic silicon thermal insulation coating. Furthermore, the component A of the present invention also includes: 0.05 to 1 parts of red iron oxide, which has good tinting power. By adding red iron oxide to the component A, it is convenient for users to distinguish the components A and B by color, which is convenient for use. Among them, the silane coupling agent also includes 0-0.5 parts of silane coupling agent 1 and 0-0.5 parts of silane coupling agent 2, calculated by mass. One end of silane coupling agent 1 can form a chemical bond with the group on the surface of the powder, and the other end can react and bond with the resin; silane coupling agent 2 can also undergo condensation cross-linking on the above basis, further improving the bonding strength between the powder and the resin matrix, and the hydrolysis product can further improve the hydrophobic properties of the powder.
[0059] Furthermore, in each of the above embodiments, component A and component B satisfy at least one of the following conditions:
[0060] The particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1;
[0061] The mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm;
[0062] The glass powder includes glass powder 1 and glass powder 2, the mass ratio of glass powder 1 to glass powder 2 is 3:1-6:1, the particle size of glass powder 1 is 1-5 μm, and the particle size of glass powder 2 is 15-30 μm;
[0063] The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
[0064] Specifically, when the components A and B of the present invention only meet one condition, for example, the components A and B meet the following conditions: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1. Through the above control, the low thermal conductivity of air can be effectively reduced to achieve thermal insulation.
[0065] When the components A and B of the present invention only meet two conditions, for example, the components A and B meet the following conditions: the particle size of wollastonite is 5 to 20 μm, the aspect ratio of wollastonite is 10:1 to 30:1; and the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm. The present invention can optimize the pore structure and pore size distribution by controlling the particle size, aspect ratio and combination of mica powders of different particle sizes of wollastonite, so that the heat conduction path in the material is more tortuous, thereby reducing the thermal conductivity.
[0066] When the components A and B of the present invention only meet three conditions, for example, the components A and B meet the following conditions: the particle size of wollastonite is 5 to 20 μm, the aspect ratio of wollastonite is 10:1 to 30:1; and the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 and mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm; and the glass powder includes glass powder 1 and glass powder 2, the mass ratio of glass powder 1 and glass powder 2 is 3:1 to 6:1, the particle size of glass powder 1 is 1 to 5 μm, and the particle size of glass powder 2 is 15 to 30 μm. Through the synergistic effect of wollastonite, mica powder and glass powder, a more compact structure is formed, air convection and heat conduction are reduced, and heat conduction and convection can be effectively blocked, so that the coating of the present invention has better thermal insulation performance.
[0067] When the components A and B of the present invention meet four conditions, that is, the components A and B of the present invention meet all the above conditions, the components A and B meet: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1; the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm; the glass powder The invention comprises glass powder 1 and glass powder 2, wherein the mass ratio of glass powder 1 to glass powder 2 is 3:1-6:1, the particle size of glass powder 1 is 1-5 μm, and the particle size of glass powder 2 is 15-30 μm; the hollow glass microspheres comprise hollow glass microspheres 1 and hollow glass microspheres 2, wherein the mass ratio of hollow glass microspheres 1 to hollow glass microspheres 2 is 3:1-6:1, the particle size of hollow glass microspheres 1 is 30-60 μm, and the particle size of hollow glass microspheres 2 is 5-20 μm. The invention controls the collocation of the different particle sizes of the above-mentioned different powders, so that the viscosity of component A and component B of the invention is lower under the same amount of powder added, thereby further improving the process performance of the subsequent preparation of the organosilicon thermal insulation coating. At the same time, due to the high filling rate in the spatial structure, the densest stacking in three-dimensional space is formed, so that the thermal insulation path formed by the thermal insulation powder is the longest, and the film-forming silicone resin can reach the maximum powder consumption, so that the prepared thermal insulation coating has good morphology maintenance ability at high temperature, and also keeps the integrity of the ceramicized porcelain good, forming a dense insulation layer, isolating convective heat transfer from external oxygen and the longest heat transfer path, reducing heat conduction, and isolating convective heat transfer to the greatest extent.
[0068] The inventor found in the experimental process that, since the traditional expanded graphite has the characteristics of large particle size and high expansion ratio after heating, the use of conventional expanded graphite in the ceramicized organic silicon thermal insulation coating can well improve the flame retardant performance, but due to the excessive expansion ratio, the overall ceramic integrity will be greatly damaged, further aggravating the heat transfer of thermal convection, thereby reducing the thermal insulation performance, and at the same time, the expanded graphite forms a continuous structure, which makes the electrical insulation performance of the thermal insulation coating significantly reduced. Therefore, the inventor found through a large number of experimental studies that when the particle size of the nano expanded graphite in the A component of the present invention is 600-900nm; the particle size of the nano expanded graphite in the B component is 600-900nm; when the particle size of the nano expanded graphite in the A component and the B component is equal, the particle size of the nano expanded graphite is small, the lamellar structure retention rate is low, the expansion ratio is low, and the ceramic integrity will not be damaged after expansion; and it is conducive to slight expansion when the volume of other components collapses to make up for the collapsed volume, and the carbon layer formed at the same time can also further reduce the thermal conductivity of the organic silicon thermal insulation coating.
[0069] Furthermore, in the components A and B of the present invention, the melting point of glass powder 1 is 380-450°C, and the melting point of glass powder 2 is 500-600°C. In the present invention, glass powder 1 and glass powder 2 are both used as a flux. Since glass powder 1 and glass powder 2 have different melting points, it is possible to match the thermal decomposition of the silicone thermal insulation coating at high temperatures at high temperatures, that is, when the thermal insulation coating undergoes partial thermal decomposition, the flux also partially melts accordingly, and fuses with the products produced by the thermal decomposition to maintain the structure of the thermal insulation coating system. When the organic components of the thermal insulation coating rapidly decompose at a higher temperature, the flux with a higher melting point also rapidly and massively melts accordingly, and fuses with the products produced by the thermal decomposition to maintain the structure of the thermal insulation coating system, maintain a dense outer isolation layer, improve the porcelain-forming effect, further enhance the thermal insulation capacity of the silicone thermal insulation coating of the present invention, and avoid the phenomenon of powder shedding.
[0070] In addition, in the above-mentioned embodiments, in component A and component B,
[0071] Vinyl silicone oil includes vinyl silicone oil 1 and vinyl silicone oil 2, the viscosity of vinyl silicone oil 1 is: 2000~5000mPa·s, and the viscosity of vinyl silicone oil 2 is: 8000~200000mPa·s; the mass content of vinyl in vinyl silicone oil is 0.03%~2.3%; preferably, the mass content of vinyl is between 0.1% and 1.0%, and more preferably, the mass content of vinyl is between 0.1% and 0.3%.
[0072] In parts by mass, in component A, the vinyl silicone oil includes 10 to 20 parts of vinyl silicone oil 1 and 10 to 20 parts of vinyl silicone oil 2, preferably, the vinyl silicone oil includes 10 to 15 parts of vinyl silicone oil 1 and 10 to 15 parts of vinyl silicone oil 2; in component B, the vinyl silicone oil includes 10 to 30 parts of vinyl silicone oil 1 and 10 to 20 parts of vinyl silicone oil 2, preferably, the vinyl silicone oil includes 20 to 30 parts of vinyl silicone oil 1 and 10 to 15 parts of vinyl silicone oil 2.
[0073] The viscosity of phenyl vinyl silicone rubber is 6000-200000 mPa·s, preferably, the viscosity is 6000-8000 mPa·s, the mass content of vinyl in phenyl vinyl silicone rubber is 0.1%-0.75%, preferably, the mass content of vinyl is 0.4%-0.6%, the molar content of phenyl is 3%-25%, preferably, the molar content of phenyl is 10%-13%, and the mass content of phenyl vinyl silicone rubber in component A and / or component B is 10%-15%, that is, the mass proportion of phenyl vinyl silicone rubber in 100 parts of component A is 10%-15%, and the mass proportion of phenyl vinyl silicone rubber in 100 parts of component B is also in the range of 10%-15%. Preferably, the mass content of phenyl vinyl silicone rubber in component A and / or component B is 12-15%; preferably, by mass, component A includes 12-18 parts of phenyl vinyl silicone rubber, and component B includes 10-13 parts of phenyl vinyl silicone rubber. In addition, the hydrogen content in the hydrogen-containing silicone oil is 0.5 wt% to 2.5 wt%, and the hydrogen content refers to the mass content of hydrogen.
[0074] The present invention adjusts and controls the physical parameters of vinyl silicone oil, phenyl vinyl silicone rubber and hydrogen-containing silicone oil, and the physical parameters include viscosity, mass content of vinyl, molar content of phenyl, hydrogen content in hydrogen-containing silicone oil, etc. This avoids the problem that the subsequent process cannot be sprayed or the difficulty of subsequent preparation of organic silicon thermal insulation coating is increased due to the excessively high viscosity of the raw material powder. As a result, the raw materials in the formula of the organic silicon thermal insulation coating of the present invention are fully reacted, and the process preparation is convenient, and the thermal insulation filler has a better cross-linked structure, and has good mechanical strength and elasticity while having high temperature resistance.
[0075] In a second aspect, the present invention provides a method for preparing an organic silicon thermal insulation coating, which is used to prepare the organic silicon thermal insulation coating of each of the above embodiments, comprising the following steps:
[0076] Preparation of component A: By mass, 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 part of inhibitor and 1 to 10 parts of PCL phase change material are mixed to obtain component A.
[0077] Preparation of component B: Mix 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 part of catalyst and 1 to 10 parts of PCL phase change material to obtain component B, based on mass percentage.
[0078] Preparation of organic silicon thermal insulation coating: Component A and component B are mixed and cured to obtain the target organic silicon thermal insulation coating.
[0079] Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
[0080] The present invention improves the simplicity of the process by separately controlling the preparation steps of component A and component B in the formula, thereby ensuring the adaptive combination of component A and component B. Through the above steps, the preparation process is simple and efficient, and it is easy to prepare an organosilicon thermal insulation coating that has both high temperature resistance and thermal insulation performance, and has good flame retardancy and insulation.
[0081] The inventors also found through experimental comparison that the steps of preparing component A and component B satisfy at least one of the following conditions:
[0082] The particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1;
[0083] The mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm;
[0084] The glass powder includes glass powder 1 and glass powder 2, the mass ratio of glass powder 1 to glass powder 2 is 3:1-6:1, the particle size of glass powder 1 is 1-5μm, and the particle size of glass powder 2 is 15-30μm; the melting point of glass powder 1 is 380-450℃, and the melting point of glass powder 2 is 500-600℃.
[0085] The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
[0086] Specifically, when the steps of preparing component A and component B of the present invention only meet one condition, for example, the steps of preparing component A and component B meet the following conditions: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1.
[0087] When the preparation steps of component A and component B of the present invention meet only two conditions, for example, the preparation steps of component A and component B meet: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1; and the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm.
[0088] When the steps of preparing component A and component B of the present invention only meet three conditions, for example, the steps of preparing component A and component B meet: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1; and the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 to 10 μm; and the glass powder includes glass powder 1 and glass powder 2, the mass ratio of glass powder 1 to glass powder 2 is 3:1 to 6:1, the particle size of glass powder 1 is 1 to 5 μm, the particle size of glass powder 2 is 15 to 30 μm, the melting point of glass powder 1 is 380 to 450°C, and the melting point of glass powder 2 is 500 to 600°C.
[0089] When the preparation steps of component A and component B of the present invention meet four conditions, that is, the preparation steps of component A and component B of the present invention meet all the above conditions, the preparation steps of component A and component B meet: the particle size of wollastonite is 5 to 20 μm, and the aspect ratio of wollastonite is 10:1 to 30:1; the mica powder includes mica powder 1 and mica powder 2, the mass ratio of mica powder 1 to mica powder 2 is 1:1 to 3:1, the particle size of mica powder 1 is 15 to 30 μm, and the particle size of mica powder 2 is 1 ~10μm; the glass powder includes glass powder 1 and glass powder 2, the mass ratio of glass powder 1 to glass powder 2 is 3:1~6:1, the particle size of glass powder 1 is 1~5μm, and the particle size of glass powder 2 is 15~30μm; the hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of hollow glass microspheres 1 to hollow glass microspheres 2 is 3:1~6:1, the particle size of hollow glass microspheres 1 is 30~60μm, and the particle size of hollow glass microspheres 2 is 5~20μm.
[0090] By controlling the different particle sizes, structures and melting points of wollastonite, mica powder, hollow glass microspheres and glass powder in the preparation steps of component A and component B, the prepared thermal insulation coating has the densest packing structure in three-dimensional space, forming a dense thermal insulation layer, which greatly improves the thermal insulation capacity of the thermal insulation coating. At the same time, under the same powder addition ratio, the components A and B obtained by the preparation method of the present invention have the lowest viscosity, making it easy to carry out process operations such as spraying and mixing to obtain the organosilicon thermal insulation coating, and the preparation process is simple and the production efficiency is improved.
[0091] The inventors also found that since the powder and vinyl silicone oil and phenyl vinyl silicone rubber are easy to form hydrogen bonds, the viscosity of the formed component A and component B is high, so that they cannot be sprayed, which increases the difficulty of preparing the coating process. Therefore, the inventors control the modification of the powder before preparing component A and component B, thereby reducing the viscosity of component A and component B while improving the dispersibility of the powder in vinyl silicone oil and phenyl vinyl silicone rubber, and enhancing the adhesion between the powder and vinyl silicone oil and phenyl vinyl silicone rubber. Specifically, the powders of wollastonite, mica powder 1, mica powder 2, glass powder 1, glass powder 2, nano-expanded graphite, nano-titanium dioxide and nano-aluminum hydroxide are modified, including the following steps:
[0092] (1) A silane coupling agent, water, ethanol and 5 wt% ammonia water are mixed in a mass ratio of 1:3:6:1 to obtain a mixed solution of silane coupling agent, water, ethanol and 5 wt% ammonia water. Thus, the pH of the hydrolysis environment is adjusted to be weakly alkaline by water and ammonia water. In the above hydrolysis environment, ethanol accelerates the hydrolysis of the silane coupling agent to form silanol groups with active groups.
[0093] (2) Mix 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide; add the mixed powder into the barrel of the airflow mill and start the airflow mill. Specifically, the mixing is carried out at a speed of 300-600 rpm for 10-30 minutes. The mixing is more uniform using the airflow mill and the process is simple.
[0094] (3) Add the mixed solution in step (1) to the atomizer of the airflow mill and perform atomization feeding. After the atomization feeding time is 20 to 40 minutes, the powder and the mixed solution are mixed for 50 to 80 minutes at a mixing temperature of 60 to 80° C., and then dried at a drying temperature of 90 to 120° C. and cooled to obtain 5 to 15 parts of modified wollastonite, 2 to 8 parts of mica powder 1, 1 to 4 parts of mica powder 2, 5 to 10 parts of glass powder 1, 1 to 4 parts of glass powder 2, 0.5 to 2 parts of nano-expanded graphite, 5 to 15 parts of nano-titanium dioxide and 5 to 15 parts of nano-aluminum hydroxide powder. Since the silane coupling agent in the mixed solution has been hydrolyzed, it can fully contact with the powder through the atomization feeding method and can react with the exposed hydroxyl groups on the surface of the powder to the greatest extent, thereby reducing the viscosity-increasing effect of the powder and enhancing the dispersibility of the powder in vinyl silicone oil and phenyl vinyl silicone rubber.
[0095] Furthermore, by modifying the powder in the above steps, the adhesion between the powder and the vinyl silicone oil and the phenyl vinyl silicone rubber is also improved.
[0096] Furthermore, the preparation method of the organosilicon thermal insulation coating comprises the following steps:
[0097] Powder modification: silane coupling agent, water, ethanol and 5wt% ammonia water are mixed to obtain a mixed solution of silane coupling agent, water, ethanol and 5wt% ammonia water; 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide are mixed by weight, and added into the mixed solution of silane coupling agent, water, ethanol and 5wt% ammonia water, and mixed by air flow mill equipment to obtain modified 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide powder.
[0098] Preparation of component A: After mixing 10-20 parts of vinyl silicone oil 1, 10-20 parts of vinyl silicone oil 2 and 10-20 parts of phenyl vinyl silicone rubber powders by mass, add 5-15 parts of modified wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano-expanded graphite, 5-15 parts of nano-titanium dioxide and 5-15 parts of nano-aluminum hydroxide powders, heat up for dehydration, cool down to stop dehydration, then add 1-10 parts of hydrogen-containing silicone oil and 0.1-1 part of inhibitor at a constant temperature, then add 5-10 parts of hollow glass microspheres 1, 1-5 parts of hollow glass microspheres 2, 0.05-1 part of red iron oxide and 1-10 parts of PCL phase change material to obtain component A. Among them, after the modified powder is mixed, the temperature is raised to 100-110°C for dehydration, and after the temperature is lowered to 40-50°C to stop dehydration, 1-10 parts of hydrogen-containing silicone oil and 0.1-1 part of inhibitor are added and mixed at a constant temperature of 40-50°C, which is beneficial to improve the dispersibility of the powder and control the viscosity of component A.
[0099] Preparation of component B: Mix 10-30 parts of vinyl silicone oil 1, 10-20 parts of vinyl silicone oil 2 and 10-15 parts of phenyl vinyl silicone rubber powders by mass, add 5-15 parts of modified wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano-expanded graphite, 5-15 parts of nano-titanium dioxide and 5-15 parts of nano-aluminum hydroxide powder, then add 5-10 parts of hollow glass microspheres 1 and 1-5 parts of hollow glass microspheres 2, heat up for dehydration, cool down to stop dehydration, add 1-10 parts of PCL phase change material at a constant temperature, add 0.1-1 part of catalyst to obtain component B. Among them, the temperature rise dehydration is to rise the temperature to 100-110°C for dehydration, the temperature drop to stop dehydration is to drop the temperature to 40-50°C to stop dehydration, and the constant temperature is to keep the temperature at 40-50°C.
[0100] Preparation of organic silicon thermal insulation coating: After mixing component A and component B, spray or scrape them on the template surface for curing to obtain the target organic silicon thermal insulation coating. The curing is drying at room temperature for 22 to 26 hours, or curing at a temperature of 60 to 70°C for 3 to 5 hours.
[0101] Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
[0102] Specifically, in the preparation process of component A and component B of the present invention, wollastonite, glass powder, mica powder, nano titanium dioxide, modified nano expanded graphite, and nano aluminum hydroxide powder are first added to the modification equipment and mixed evenly, and then modified, and finally the mixed mixture of vinyl silicone oil and phenyl vinyl silicone rubber is added in batches, and after dispersion, the speed is reduced to add the last hollow glass microspheres, PCL phase change materials and iron oxide red, etc., and dispersed at a low speed. By adding the powder in batches as described above, it is avoided that the powder proportion in component A and component B is relatively high, and it is difficult to disperse the powder evenly by adding and mixing at one time; secondly, the hollow glass microspheres in the powder have limited compressive strength, and their hollow structure will be destroyed at high speed, which will cause the viscosity of the coating to rise rapidly and the heat insulation effect to drop significantly, so it is added at the end, and the speed should be reduced to disperse at the same time to ensure that the hollow structure is not destroyed; and it is avoided that the temperature rises quickly during the stirring process of adding once, which is not conducive to temperature control and easy to gel.
[0103] The preparation method of the present invention obtains an organic silicon thermal insulation coating with both high temperature resistance and thermal insulation performance through the mutual cooperation of the above steps, and has good insulation properties, and can be used in the battery field.
[0104] The preparation method of the organosilicon thermal insulation coating of the present invention will be described in further detail below.
[0105] Example 1
[0106] a. Powder modification
[0107] (1) Silane coupling agent XA-560, water, ethanol and 5 wt% ammonia water were mixed and stirred at a mass ratio of 1:3:6:1 for 1 h, wherein the silane coupling agent was 1 part by mass, to obtain a mixed solution of silane coupling agent, water, ethanol and 5 wt% ammonia water.
[0108] (2) Add 10 to 12 parts of wollastonite, 5 parts of mica powder 1, 1.5 parts of mica powder 2, 6 parts of glass powder 1, 1.4 parts of glass powder 2, 0.8 parts of nano-expanded graphite, 5 to 15 parts of nano-titanium dioxide and 10 parts of nano-aluminum hydroxide into a high-speed disperser for mixing; mix at a speed of 500 rpm for 15 minutes, add the mixed powder into the barrel of a jet mill, and start the jet mill.
[0109] (3) adding the mixed solution in step (1) into the atomizer of the air flow mill and performing atomization feeding. After the atomization feeding time is 30 minutes, the powder and the mixed solution are mixed for 60 minutes at a mixing temperature of 60 to 80° C., and then dried at a drying temperature of 100° C. and cooled to obtain 10 to 12 parts of modified wollastonite, 5 parts of mica powder 1, 1.5 parts of mica powder 2, 6 parts of glass powder 1, 1.4 parts of glass powder 2, 0.8 parts of nano expanded graphite, 5 to 15 parts of nano titanium dioxide and 10 parts of nano aluminum hydroxide powder.
[0110] bA component preparation
[0111] By mass, mix 15 parts of vinyl silicone oil 1, 10 parts of vinyl silicone oil 2 and 15 parts of phenyl vinyl silicone rubber in a Double Star mixer, set the rotation speed to 2000rmp / min, the revolution speed to 300rmp / min, and mix for 5min. Add 10 parts of modified wollastonite, 5 parts of mica powder 1, 1.5 parts of mica powder 2, 6 parts of glass powder 1, 1.4 parts of glass powder 2, 0.8 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 10 parts of nano aluminum hydroxide powder into the Double Star mixer in 4 batches, and stir for 10min after each batch is added. After all the modified powders are added and stirring is maintained, heat to 105℃, and turn on vacuum to dehydrate for 1h. Keep vacuuming and dehydrating, turn on the circulating cooling water to cool down, and turn off the vacuum after cooling to 40℃. Then, add 7 parts of hydrogen-containing silicone oil (hydrogen content of 0.5% to 2.5%) and 0.2 parts of inhibitor at a constant temperature of 40°C and stir and mix for 10 minutes. Then, add 7.5 parts of hollow glass microspheres 1, 2 parts of hollow glass microspheres 2, 0.1 parts of red iron oxide and 7.5 parts of PCL phase change material and stir and mix for 10 minutes. Turn off the circulating cooling water, turn off the rotation and revolution stirring, and obtain component A.
[0112] Preparation of cB component
[0113] By mass, 25 parts of vinyl silicone oil 1, 10 parts of vinyl silicone oil 2 and 10 parts of phenyl vinyl silicone rubber are mixed in a Double Star mixer, the rotation speed is set to 2000rmp / min, the revolution speed is set to 300rmp / min, and the mixing time is 5min. Add 12 parts of modified wollastonite, 5 parts of mica powder 1, 1.5 parts of mica powder 2, 6 parts of glass powder 1, 1.4 parts of glass powder 2, 0.8 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 10 parts of nano aluminum hydroxide powder into the Double Star mixer in 4 batches, and stir for 10min after each batch is added. Then add 7.5 parts of hollow glass microspheres 1 and 2 parts of hollow glass microspheres 2, mix, heat to 105℃, and turn on vacuum to dehydrate for 1h. Keep vacuuming and dehydrating, turn on the circulating cooling water to cool down, and turn off the vacuum after cooling to 40℃. Then, 7.3 parts of PCL phase change material were added at a constant temperature of 40° C. and stirred for 10 minutes, and then 0.5 parts of a platinum catalyst with a concentration of 1000 ppm were added and stirred for 10 minutes to obtain component B.
[0114] d. Example 1 Preparation of silicone thermal insulation coating
[0115] Weigh 30g-50g of the prepared component A into a beaker, then add 30g-50g of component B into the beaker, and the mass ratio of component A to component B is 100:100, and stir and mix at a speed of 2000rmp / min for 30s. Apply the mixed component A and component B on a 1mm thick aluminum plate by scraping or spraying, and dry at room temperature for 24h or at 60°C for 4h until it is completely cured, to obtain the silicone thermal insulation coating of Example 1.
[0116] Among them, in the steps of preparing component A and component B, the vinyl silicone oil includes vinyl silicone oil 1 and vinyl silicone oil 2, the viscosity of vinyl silicone oil 1 is: 2000~5000mPa·s, and the viscosity of vinyl silicone oil 2 is: 8000~200000mPa·s; the mass content of vinyl in the vinyl silicone oil is 0.03%~2.3%; the viscosity of phenyl vinyl silicone rubber is: 6000~200000mPa·s, the mass content of vinyl in the phenyl vinyl silicone rubber is 0.1%~0.75%, and the molar content of phenyl is 3%~25%.
[0117] The formula of the silicone thermal insulation coating of Example 1 is shown in Table 1.
[0118] Table 1. Formula of silicone thermal insulation coating of Example 1
[0119] raw material Component A Component B Vinyl silicone oil 1 15 25 Vinyl silicone oil 2 10 10 Hydrogen silicone oil 7 0 Phenyl Vinyl Silicone Rubber 15 10 Hollow glass microspheres1 7.5 7.5 Hollow glass microspheres 2 2 2 Nano Expanded Graphite 0.8 0.8 Nano Aluminum Hydroxide 10 10 Nano Titanium Dioxide 10 10 Glass powder 1 6 6 Glass powder 2 1.4 1.4 Mica powder 1 (sericite) 5 5 Mica powder 2 (sericite) 1.5 1.5 Wollastonite 10 12 Iron oxide red 0.1 0 Silane coupling agent 1 0.5 0.5 Silane coupling agent 2 0.5 0.5 PCL phase change material 7.5 7.3 Inhibitors 0.2 0 catalyst 0 0.5 total 110 110
[0120] The formula of the silicone thermal insulation coating of Example 2 is shown in Table 1.
[0121] The difference between Example 2 and Example 1 is that in the formula of Example 2, both component A and component B contain only one type of glass powder 2, and no glass powder 1 is added. The formula of Example 2 is shown in Table 2.
[0122] Table 2. Formula of silicone thermal insulation coating of Example 2
[0123] raw material Component A Component B Vinyl silicone oil 1 15 25 Vinyl silicone oil 2 10 10 Hydrogen silicone oil 7 0 Phenyl Vinyl Silicone Rubber 15 10 Hollow glass microspheres1 7.5 7.5 Hollow glass microspheres 2 2 2 Nano Expanded Graphite 0.8 0.8 Nano Aluminum Hydroxide 10 10 Nano Titanium Dioxide 10 10 Glass powder 1 0 0 Glass powder 2 7.4 7.4 Mica powder 1 (sericite) 5 5 Mica powder 2 (sericite) 1.5 1.5 Wollastonite 10 12 Iron oxide red 0.1 0 Silane coupling agent 1 0.5 0.5 Silane coupling agent 2 0.5 0.5 PCL phase change material 7.5 7.3 Inhibitors 0.2 0 catalyst 0 0.5 total 110 110
[0124] Comparative Example 1
[0125] The difference between Comparative Example 1 and Example 1 is that in the formula of Comparative Example 1, component A does not have 2 hollow glass microspheres, 2 mica powders, 2 glass powders, and nano-expanded graphite, and component B does not have 2 hollow glass microspheres, 2 mica powders, 2 glass powders, and nano-expanded graphite, so Comparative Example 1 cannot regulate the combination of different particle sizes of different powders. The formula of Comparative Example 1 is shown in Table 3.
[0126] Table 3 Comparative Example 1 Formula of organic silicon thermal insulation coating
[0127] raw material Component A Component B Vinyl silicone oil 1 15 25 Vinyl silicone oil 2 10 10 Hydrogen silicone oil 7 0 Phenyl Vinyl Silicone Rubber 15 10 Hollow glass microspheres1 9.5 9.5 Nano Aluminum Hydroxide 10.8 10.8 Nano Titanium Dioxide 10 10 Glass powder 1 7.4 7.4 Mica powder 1 (sericite) 6.5 6.5 Wollastonite 10 12 Iron oxide red 0.1 0 Silane coupling agent 1 0.5 0.5 Silane coupling agent 2 0.5 0.5 PCL phase change material 7.5 7.3 Inhibitors 0.2 0 catalyst 0 0.5 total 110 110
[0128] Comparative Example 2
[0129] The difference between Comparative Example 2 and Example 1 is that in the formula of Comparative Example 2, component A does not contain PCL phase change material, and component B does not contain PCL phase change material. The formula of Comparative Example 2 is shown in Table 4.
[0130] Table 4. Formula of silicone thermal insulation coating of comparative example 2
[0131] raw material Component A Component B Vinyl silicone oil 1 15 25 Vinyl silicone oil 2 10 10 Hydrogen silicone oil 7 0 Phenyl Vinyl Silicone Rubber 15 10 Hollow glass microspheres1 7.5 7.5 Hollow glass microspheres 2 2 2 Nano Expanded Graphite 0.8 0.8 Nano Aluminum Hydroxide 10 10 Nano Titanium Dioxide 10 10 Glass powder 1 6 6 Glass powder 2 1.4 1.4 Mica powder 1 (sericite) 5 5 Mica powder 2 (sericite) 1.5 1.5 Wollastonite 10 12 Iron oxide red 0.1 0 Silane coupling agent 1 0.5 0.5 Silane coupling agent 2 0.5 0.5 Inhibitors 0.2 0 catalyst 0 0.5 total 102.5 102.5
[0132] Comparative Example 3
[0133] Purchase commercially available water-based epoxy steel structure fire retardant coating.
[0134] Comparative Example 4
[0135] Purchase commercially available aerogel thermal insulation coating.
[0136] The shear strength, density, thermal conductivity, volume shrinkage, porcelain formation, back temperature T1, temperature rise curve and insulation resistance of different embodiments and comparative examples were tested. The specific test methods and test standards of different test items are shown in Table 5. The test results are shown in Table 6.
[0137] Table 5. Test methods and test standards for different test items
[0138]
[0139] Table 6. Measurement results of examples and comparative examples
[0140]
[0141] From Table 6, we can see that the specific results are as follows:
[0142] The embodiment of the present invention has good insulation performance, shear strength and volume shrinkage, and the density is 1.0-1.50g / cm 3. Among them, compared with Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3, Example 1 has the smallest thermal conductivity. This is because in Example 1, the gaps between the raw materials are filled with small-particle powders by matching the large and small particle sizes of the hollow glass microspheres, mica powder, and glass powder. In Comparative Example 1, the gaps between the powders are filled with silicone resin, and the intrinsic thermal conductivity of silicone resin is about 0.1W / m·K, which is much higher than the thermal conductivity of the hollow glass microspheres of the thermal insulation filler 0.04W / m·K. Therefore, the thermal conductivity of Comparative Example 1 is higher than that of Example 1; the formulas of Example 1 and Example 2 differ in glass powder. Because Example 1 uses glass powder 1 with a smaller particle size, the intrinsic thermal conductivity of glass powder 2 is slightly higher than that of glass powder 1. Therefore, compared with Example 2, Example 1 has a smaller thermal conductivity and better thermal insulation performance. Compared with Comparative Example 2, in Example 1, due to the addition of PCL phase change material in the formula, part of the heat is absorbed by the phase change of the phase change material during the thermal conductivity test, which does not cause the temperature of the test sample to rise. Therefore, the thermal conductivity of the test is lower than that of Comparative Example 2. In addition, in Example 1, by matching different powder particle sizes and adding phase change heat absorbing materials, the heat conduction path of the coating is reduced to a certain extent, thereby having better thermal insulation performance. Figure 1 As shown, the blank iron plate is used as the blank control group. It can be seen that the thermal insulation temperature difference of Example 1 of the present invention is greater than that of Comparative Examples 1-4. That is to say, Example 1 of the present invention has better thermal insulation performance than Comparative Examples 1-4.
[0143] Comparative Example 3 is a purchased water-based epoxy steel structure fire retardant coating, which is cured on glass fiber cloth by adding powder filler to the silicone resin system. Because there is no need to consider the bonding problem between the thermal insulation pad and the substrate, such as applying it to the surface of the substrate by adhesive, the amount of thermal insulation filler added can be higher. Because it is reinforced with glass fiber cloth, its mechanical properties such as tensile strength are higher than those of Example 1 and Comparative Examples 1 and 2, but because the thermal conductivity of the glass fiber itself is very high, the overall thermal conductivity of Comparative Example 3 is the highest. However, thanks to its good mechanical strength and the ultra-high content of thermal insulation filler in the powder filler, and the fact that the value of the back temperature T1 of Comparative Example 2 is lower than that of Comparative Example 1 and the value of the thermal insulation temperature difference is higher than that of Comparative Example 1, it can be seen that its comprehensive thermal insulation effect is better than that of Comparative Example 1, but it is still far less than that of Example 1 of the present invention.
[0144] Comparative Example 4 is a purchased aerogel thermal insulation coating, which is a thermal insulation coating with high attention in the market. Its composition is a large amount of aerogel powder added to the film-forming part, supplemented by a small amount of additives to disperse the aerogel powder. Generally, water is added as a dispersant to reduce the viscosity. Its film-forming material is an inorganic silicate sol, which is an inorganic phase after curing. Therefore, it has good flame impact resistance and almost no morphology and size changes after high temperature impact. Due to the large amount of aerogel powder added, it also has good thermal insulation performance. Compared with Example 1, its disadvantages are as follows:
[0145] (1) Comparative Example 4 is an inorganic system, which is hard and brittle after curing, and has no toughness and resilience. When used between battery cells, the assembly force between the battery cells acts on the cured coating, causing the coating to break. After the breakage, a large amount of heat will be transferred from the broken gaps, affecting the thermal insulation effect.
[0146] (2) Due to the addition of water as a dispersant, the curing speed is slow, and surface cracking is prone to occur during high-temperature curing.
[0147] (3) The thermal conductivity of Comparative Example 4 is significantly lower than that of Example 1, which is only 0.086 W / m·K. However, judging from the back surface temperature T1 of the experimental test, its thermal insulation effect is not as good as that of Example 1. The thermal insulation temperature difference at 900°C is only 739°C, which is lower than 758°C of Example 1.
[0148] It can be seen from the above three points that Example 1 and Example 2 have better performance than Comparative Example 4 under the heat insulation condition between battery cells.
[0149] Although the present invention has been illustrated and described with reference to certain preferred embodiments of the present invention, it should be understood by those skilled in the art that the above is a further detailed description of the present invention in conjunction with specific embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Those skilled in the art may make various changes in form and details, including making several simple deductions or substitutions, without departing from the spirit and scope of the present invention.
Claims
1. An organic silicon thermal insulation coating, characterized in that: It includes component A and component B; In parts by mass, the component A includes: 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 parts of inhibitor, and 1 to 10 parts of PCL phase change material; In parts by mass, the B component includes: 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 parts of catalyst, and 1 to 10 parts of PCL phase change material; The surfaces of the nano-expanded graphite in the A component and the B component have an insulating layer; and the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
2. The organic silicon thermal insulation coating according to claim 1, characterized in that: In parts by mass, the component A further comprises: 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide, and the component B further comprises: 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide.
3. The organic silicon thermal insulation coating according to claim 2, characterized in that: In parts by mass, the component A further comprises: 0.1 to 1.5 parts of a silane coupling agent and 0.05 to 1 parts of red iron oxide; the component B further comprises: 0.1 to 1.5 parts of a silane coupling agent.
4. The organic silicon thermal insulation coating according to claim 1, characterized in that: The A component and the B component satisfy at least one of the following conditions: The particle size of the wollastonite is 5 to 20 μm, and the aspect ratio of the wollastonite is 10:1 to 30:1; The mica powder comprises mica powder 1 and mica powder 2, the mass ratio of the mica powder 1 to the mica powder 2 is 1:1 to 3:1, the particle size of the mica powder 1 is 15 to 30 μm, and the particle size of the mica powder 2 is 1 to 10 μm; The glass powder includes glass powder 1 and glass powder 2, the mass ratio of the glass powder 1 to the glass powder 2 is 3:1-6:1, the particle size of the glass powder 1 is 1-5 μm, and the particle size of the glass powder 2 is 15-30 μm; The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
5. The organic silicon thermal insulation coating according to claim 4, characterized in that: In the A component, the particle size of the nano-expanded graphite is 600-900 nm; in the B component, the particle size of the nano-expanded graphite is 600-900 nm; the particle sizes of the nano-expanded graphite in the A component and the B component are equal.
6. The organic silicon thermal insulation coating according to claim 4, characterized in that: In the A component and the B component, the melting point of the glass powder 1 is 380-450°C, and the melting point of the glass powder 2 is 500-600°C.
7. The organic silicon thermal insulation coating according to claim 1, characterized in that: In the A component and the B component, The vinyl silicone oil comprises vinyl silicone oil 1 and vinyl silicone oil 2, wherein the viscosity of the vinyl silicone oil 1 is 2000-5000 mPa·s, and the viscosity of the vinyl silicone oil 2 is 8000-200000 mPa·s; the mass content of vinyl in the vinyl silicone oil is 0.03%-2.3%; in terms of mass parts, in component A, the vinyl silicone oil comprises 10-20 parts of the vinyl silicone oil 1 and 10-20 parts of the vinyl silicone oil 2, and in component B, the vinyl silicone oil comprises 10-30 parts of the vinyl silicone oil 1 and 10-20 parts of the vinyl silicone oil 2; The viscosity of the phenyl vinyl silicone rubber is 6000-200000 mPa·s, the mass content of vinyl in the phenyl vinyl silicone rubber is 0.1%-0.75%, the molar content of phenyl is 3%-25%, and the mass content of the phenyl vinyl silicone rubber in the component A and / or the component B is 10%-15%; The hydrogen content of the hydrogen-containing silicone oil is 0.5wt% to 2.5wt%.
8. The method for preparing the organic silicon thermal insulation coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Preparation of component A: by weight, 20 to 40 parts of vinyl silicone oil, 10 to 20 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 1 to 10 parts of hydrogenated silicone oil, 0.1 to 1 parts of inhibitor and 1 to 10 parts of PCL phase change material are mixed to obtain component A; Preparation of component B: by weight, 20 to 50 parts of vinyl silicone oil, 10 to 15 parts of phenyl vinyl silicone rubber, 5 to 15 parts of wollastonite, 2 to 8 parts of mica powder, 5 to 10 parts of glass powder, 0.5 to 2 parts of nano-expanded graphite, 1 to 15 parts of hollow glass microspheres, 0.1 to 1 part of catalyst and 1 to 10 parts of PCL phase change material are mixed to obtain component B; Preparation of organic silicon thermal insulation coating: mixing and curing the component A and the component B to obtain the target organic silicon thermal insulation coating; Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
9. The method for preparing the organic silicon thermal insulation coating according to claim 8, characterized in that: The steps of preparing component A and component B satisfy at least one of the following conditions: The particle size of the wollastonite is 5 to 20 μm, and the aspect ratio of the wollastonite is 10:1 to 30:1; The mica powder comprises mica powder 1 and mica powder 2, the mass ratio of the mica powder 1 to the mica powder 2 is 1:1 to 3:1, the particle size of the mica powder 1 is 15 to 30 μm, and the particle size of the mica powder 2 is 1 to 10 μm; The glass powder includes glass powder 1 and glass powder 2, the mass ratio of the glass powder 1 to the glass powder 2 is 3:1-6:1, the particle size of the glass powder 1 is 1-5 μm, the particle size of the glass powder 2 is 15-30 μm, the melting point of the glass powder 1 is 380-450° C., and the melting point of the glass powder 2 is 500-600° C.; The hollow glass microspheres include hollow glass microspheres 1 and hollow glass microspheres 2, the mass ratio of the hollow glass microspheres 1 to the hollow glass microspheres 2 is 3:1-6:1, the particle size of the hollow glass microspheres 1 is 30-60 μm, and the particle size of the hollow glass microspheres 2 is 5-20 μm.
10. The method for preparing the organic silicon thermal insulation coating according to claim 9, characterized in that: The following steps are involved: Powder modification: mixing a silane coupling agent, water, ethanol and 5wt% ammonia water to obtain a mixed solution of the silane coupling agent, water, ethanol and 5wt% ammonia water, mixing 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide by weight, adding the mixture of the silane coupling agent, water, ethanol and 5wt% ammonia water to mix by using a jet mill to obtain modified 5-15 parts of wollastonite, 2-8 parts of mica powder 1, 1-4 parts of mica powder 2, 5-10 parts of glass powder 1, 1-4 parts of glass powder 2, 0.5-2 parts of nano expanded graphite, 5-15 parts of nano titanium dioxide and 5-15 parts of nano aluminum hydroxide powder; Preparation of component A: After mixing 10 to 20 parts of vinyl silicone oil 1, 10 to 20 parts of vinyl silicone oil 2 and 10 to 20 parts of phenyl vinyl silicone rubber, add 5 to 15 parts of modified wollastonite, 2 to 8 parts of mica powder 1, 1 to 4 parts of mica powder 2, 5 to 10 parts of glass powder 1, 1 to 4 parts of glass powder 2, 0.5 to 2 parts of nano expanded graphite, 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide powder, and heat to dehydrate. After cooling to stop dehydration, add 1 to 10 parts of hydrogen-containing silicone oil and 0.1 to 1 part of inhibitor at a constant temperature, and then add 5 to 10 parts of hollow glass microspheres 1, 1 to 5 parts of hollow glass microspheres 2, 0.05 to 1 part of red iron oxide and 1 to 10 parts of PCL phase change material to obtain component A; Preparation of component B: by weight, 10 to 30 parts of vinyl silicone oil 1, 10 to 20 parts of vinyl silicone oil 2 and 10 to 15 parts of phenyl vinyl silicone rubber are mixed, and then 5 to 15 parts of the modified wollastonite, 2 to 8 parts of mica powder 1, 1 to 4 parts of mica powder 2, 5 to 10 parts of glass powder 1, 1 to 4 parts of glass powder 2, 0.5 to 2 parts of nano expanded graphite, 5 to 15 parts of nano titanium dioxide and 5 to 15 parts of nano aluminum hydroxide powder are added, and then 5 to 10 parts of hollow glass microspheres 1 and 1 to 5 parts of hollow glass microspheres 2 are added, and the mixture is heated and dehydrated, and after the temperature is lowered to stop the dehydration, 1 to 10 parts of PCL phase change material are added at a constant temperature and mixed, and 0.1 to 1 part of catalyst is added and mixed to obtain component B; Preparation of organic silicon thermal insulation coating: after mixing the component A and the component B, spraying them on the surface of the template and curing them, to obtain the target organic silicon thermal insulation coating; Among them, in the steps of preparing component A and component B, the nano-expanded graphite also includes an insulating coating treatment before the steps of preparing component A and component B; the PCL phase change material is one or more of higher aliphatic hydrocarbons, fatty acids and fatty acid esters.
Citation Information
Patent Citations
Two-component heat conducting silicon grease capable of being prepared in a gelatinization mode under normal temperature or heating condition and preparing method thereof
CN106221236A
Encapsulating silica gel and preparation method and application thereof
CN108410416A
Single-component phase-change organic silicon heat-conducting gel and preparation method thereof
CN115785677A
Organic silicon heat-proof coating based on hollow nano-microspheres and preparation method of organic silicon heat-proof coating
CN118725733A
Heat-resistant coating composition
JP1999279488A
Cited By
Preparation process of bi-component organic silicon online foaming ceramic material
CN121203406A